2013
DOI: 10.2215/cjn.07190712
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Lifestyle Factors and Medical Conditions Associated with Urinary Citrate Excretion

Abstract: SummaryBackground and objectives Lower urinary citrate excretion is a risk factor for nephrolithiasis and associated with metabolic acidosis and higher prevalence of hypertension and insulin resistance. This study sought to quantify the independent predictors of urinary citrate excretion in population-based cohorts.Design, setting, participants, & measurements A cross-sectional study of 2561 individuals from the Health Professionals Follow-Up Study and Nurses' Health Studies I and II who provided two 24-hour u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 51 publications
1
12
0
3
Order By: Relevance
“…We found thiazide use associated with decreased urinary citrate, as previously shown (Mandel et al. ). This is likely caused by thiazide‐induced hypokalemia, which would stimulate citrate reabsorption in the proximal tubules (Zuckerman and Assimos ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found thiazide use associated with decreased urinary citrate, as previously shown (Mandel et al. ). This is likely caused by thiazide‐induced hypokalemia, which would stimulate citrate reabsorption in the proximal tubules (Zuckerman and Assimos ).…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, Mandel and colleagues found having high BMI was associated with a lower urinary citrate (Mandel et al. ). Since we found an effect of weight, but not BMI on urinary citrate in the main effects model, it suggests that body habitus is important.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Not only this, other studies which are conducted in two different countries also supported the association of carbohydrate-rich food with kidney stone disease, they reported that kidney stone disease had a strong significant correlation with higher intake of cereals, grains, and caffeine (Amin et al 2017;Ryu et al 2017). Coming to the prevention of kidney stone formation, increase intake of fruits and vegetables lower the risk of kidney stone (Meschi et al 2004;Salmeh et al 2012;Yasui et al 2013;Mandel et al 2013) whereas green leafy vegetables which have higher amount of oxalate contains are also risk factors for the formation of kidney stone, consumption of leafy vegetables that contain high oxalate, more than three times per day also resulted in the formation of kidney stones in both men and women (Dai et al 2013). Less physical activity is also one of the major risk factors for the formation of kidney stone disease.…”
Section: Resultsmentioning
confidence: 77%
“…Nonetheless, hypertension, diabetes mellitus and chronic kidney disease (CKD) were proved to be correlated with nephrolithiasis. Many authors agree and it is our firm belief that stones in patients with CKD should be cleared [5]. However, the risk factor that may influence the calculus kidney damage is still unclear and needs further evaluation.…”
Section: Introductionmentioning
confidence: 96%